Pengaruh Self Efficacy dan Prestasi Belajar terhadap Minat Melanjutkan Pendidikan ke Perguruan Tinggi pada Siswa SMKN 48 Jakarta - Septi Lis Anandita; Santi Susanti; Marsofiyati Marsofiyati (Politeknik Kampar, 2025)
This study aims to determine the influence of self-efficacy and academic achievement on students’ interest in pursuing higher education at SMK Negeri 48 Jakarta. The research used a quantitative approach with a survey method and questionnaire as the main instrument. The sample consisted of 168 eleventh-grade students selected through stratified random sampling. The results showed that self-efficacy had a positive and significant effect on students' interest in continuing education, while academic achievement had a positive but not statistically significant partial effect. However, both variables simultaneously had a significant influence on students' interest in higher education. These findings emphasize the importance of self-confidence and academic success in shaping students’ readiness and motivation to pursue further education. This research is expected to serve as a reference for schools and parents in providing both psychological and academic support to students.